Sukuk Market and Economic Welfare Nexus: A Partial Equilibrium Approach - Boukhatem, Jamel (International Journal of Economics and Financial Issues, 2021)
Due to its distinctive features and investment quality, sukuk as an Islamic alternative to bond financing, have known last decades a worldwide interest and a rapid widespread, particularly after the 2007-2008 global financial crisis. Despite the global market prevalence of sukuk, the literature on the sukuk – economic wealth nexus still inexistant. In this study, we develop a basic model that captures the welfare effects of sukuk markets. The main finding shows the importance of a well-developed sukuk market in hedging interest rate and inflation risks effectively and, thereby improving investor welfare. Keywords: Sukuk, Economic welfare, Partial equilibrium JEL Classifications: D53 G15 D60 DOI: https://doi.org/10.32479/ijefi.11507